Electrostatic assemblies of molecularly imprinted polymers on the surface of electrospun nanofiber membranes for the point-of-care detection of thiodiglycol, a sulfur mustard poisoning metabolic marker. Issue 12 (14th March 2023) - Luo, Yu Jie; Ye, Qi Chao; Xie, Tian Jin; Tian, Li Li; Yan, Yuan; Lei, Zhan; Wang, Dong Mei; Huang, Cheng Zhi; Li, Yuan Fang; Zhen, Shu Jun
Abstract : In this study, a new method for the point-of-care testing of thiodiglycol (TDG) using molecularly imprinted polymer (MIP)-coated electrospun nanofiber membranes is reported. Abstract : In this study, molecularly imprinted polymers (MIPs) were assembled on the surface of ethylene imine polymer (PEI)/poly(vinyl alcohol) (PVA) electrospun nanofiber membranes for the point-of-care testing (POCT) of thiodiglycol (TDG), a sulfur mustard poisoning metabolic marker, using concentrated gold nanoparticles (AuNPs) as the signal reporting units. The MIPs/PEI/PVA nanofiber membranes could capture TDG specifically through the recognition interaction between MIPs and TDG. Then, AuNPs were adsorbed onto the MIPs/PEI/PVA nanofiber membranes through the Au–S interaction between TDG and AuNPs to produce a visible red color. In order to improve the sensitivity, the silver-enhanced solutions were used to deepen the color of the nanofiber membranes and the software Image J was used to read the gray value as the signal response for subsequent analysis. There was a good linear relationship between the color change of the MIPs/PEI/PVA nanofiber membranes and the TDG concentration from 0.1 ng mL −1 to 1.0 μg mL −1, and the limit of detection was 38 pg mL −1 . This method was applied for the selective detection of TDG in urine, showing great potential for the clinical diagnosis of mustard gas poisoning.